Pengungkapan Sustainability Reporting, Intellectual Capital, dan Nilai Perusahaan - Dewi, Putu Purnama; Dewi, Kadek Ayu Kreistya (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p20, 2022)
The study aims to determine the effect of sustainability reporting and intellectual capital disclosures on the value of mining companies listed on the Indonesia Stock Exchange in 2016-2020. This research used a purposive sampling technique in taking the sample using several relevant criteria. Obtained 35 observations as a research sample. The analysis technique used is multiple linear regression. The results of the study explain that the variable disclosure of sustainability reporting and intellectual capital has a positive and significant effect on firm value. Keywords: Disclosure of  Sustainability Reporting; Intellectual Capital; Firm Value.